Network routing with path vector protocols theory and applications. - Sobrinho, João Luis (Computer communication review.)
Path vector protocols are currently in the limelight, mainly because the inter-domain routing protocol of the Internet, BGP (Border Gateway Protocol), belongs to this class. In this paper, we cast the operation of path vector protocols into a broad algebraic framework and relate the convergence of the protocol, and the characteristics of the paths to which it converges, with the monotonicity and isotonicity properties of its path compositional operation. Here, monotonicity means that the weight of a path cannot decrease when it is extended, and isotonicity means that the relationship between the weights of any two paths with the same origin is preserved when both are extended to the same node. We show that path vector protocols can be made to converge for every network if and only if the algebra is monotone, and that the resulting paths selected by the nodes are optimal if and only if the algebra is isotone as well.Many practical conclusions can be drawn from instances of the generic algebra. For performance-oriented routing, typical in intra-domain routing, we conclude that path vector protocols can be made to converge to widest or widest-shortest paths, but that the composite metric of IGRP (Interior Gateway Protocol), for example, does not guarantee convergence to optimal paths. For policy-based routing, typical in inter-domain routing, we formulate existing guidelines as instances of the generic algebra and we propose new ones. We also show how a particular instance of the algebra yields a sufficient condition for signaling correctness of internal BGP.